Determinants of Quality of Life among Rural Elderly Population in Khonkean Province of Thailand - Yodmai, Korravarn; Somrongthong, Ratana; Kumar, Ramesh (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To explore the factors influencing the quality of life among the elderly population of rural Thailand. METHODOLOGY: This cross-sectional study was conducted at Khon Kean Province, Thailand in one month of time period. Non-probability sampling technique was adopted by including four hundred twenty-eight elderly people age of sixty and above in this study. They were invited through available list with health department and willing participants were enrolled after taking their written consent. Those who were sick during the time of study were excluded. The quality of Life (QOL) was assessed through WHOQOL-OLD questionnaire. Chi-square was used to analyze the factors associated with the QOL in aging. Study was ethically approved from Mahidol University Thailand. RESULTS: A total of 428 elderly with a mean age of 78 years (±4) were included in this study. The results found that over 361(84%) of the elderly had moderate QOL, around 59(13.8 %) of respondents replied they had a good quality of life and 6(1.6%) had fair QOL. Factors influencing the QOL among the elderly included marital status, most were married (62.9 %), followed by divorced, widowed and single (37.1%), sufficient income (69.2%), savings, sufficient money for health care services, and needed to work. CONCLUSION: Study concluded that the factors like marital status, sufficient income, savings, healthcare services are influencing the quality of life among aging in Thailand.